Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is a specific substrate of yeast metacaspase - Silva, Alexandra (2011)
Yeast metacaspase (Yca1p) is required for the execution of apoptosis upon a wide range of stimuli. However, the specific degradome of this yeast protease has not been unraveled so far. By combining different methodologies described as requisites for a protein to be considered a protease substrate, such as digestome analysis, cleavage of recombinant GAPDH by metacaspase and evaluation of protein levels in vivo, we show that upon H2O2-induced apoptosis, the metabolic enzyme glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is a specific target of metacaspase. Nitric oxide (NO) signaling, which mediates H2O2-induced apoptosis, is required for metacaspase specific GAPDH cleavage. In conclusion, in this work we identified GAPDH as the first direct yeast metacaspase substrate described so far. Although mammalian caspases and yeast metacaspase apparently have distinct target cleavage sites, GAPDH arises as a common substrate for these proteases.